Extensive amalgam tattoo (amalgam pigmentation) on the palatal mucosa: a short case report - Kamal Fiqhi Mohammed; Essaoudi Mohammed Amine; Khalfi Lahcen; Elkhatib Karim (EDP Sciences, 2019)
Introduction: An amalgam tattoo is the most common form of exogenous oral pigmentation caused by the diffusion of dental amalgam into the soft tissue. Observation: Here we describe a case of diffuse pigmentation of amalgam on the hard palate. Discussion: Mucosal hyperpigmentation can occasionally be confused with melanotic lesions, thereby requiring a biopsy for differential diagnosis. Once the diagnosis of an amalgam tattoo has been established, the removal of the lesion is not necessary, except for aesthetic reasons.